Biocompatibility and mechanical properties of an experimental E-glass fiber-reinforced composite for dentistry - Sunarintyas, Siti (Elsevier Ltd, 2022)
Objectives: To evaluate the biocompatibility and mechanical properties of experimental bis-phenol-A and bis-GMA free E-glass fiber-reinforced composites (FRCs) prepared with hexanediol dimethacrylate (HDDMA) based resin. Methods: Two ratios of HDDMA/TEGDMA resin were evaluated: exp-1 (70/30 wt.%) and exp-2 (50/50 wt.%) with two bis-GMA resin control groups (bis-GMA/MMA and bis-GMA/TEGDMA resins, both 70/30 wt.%). E-glass fibers were embedded into the resins to prepare FRCs specimens. Biocompatibility was assessed for cytoviability and biofilm formation with Streptococcus mutans, Streptococcus sanguinis, Enterococcus faecalis, and Candida albicans. Mechanical properties were evaluated for flexural strength and hardness (24 h, water storage 1 and 28 days), water sorption (1, 7, 14, and 28 days), contact angle, and surface roughness. The data were analyzed statistically by one-way and two-way ANOVA (p < 0.05). Results: Cytoviability of the experimental groups was significantly higher than the control groups (p < 0.05). The exp-1 cytoviability (98.2 1.3%) met the ISO 10993-5 standard requirement for noncytotoxic materials. The adherence of bacteria to the experimental FRCs was visibly less than the controls, while Candida albicans adhered visibly more to the experimental groups than the controls (p < 0.05). Flexural strength showed slightly higher values for controls than for the experimental groups. The exp-1 hardness value was significantly higher in the control groups for all storage conditions (p < 0.05). The water sorption of the experimental groups was significantly higher than the controls. The surface roughness indicated no significant difference (p ¼ 0.87). The exp-1 showed a higher contact angle with the control groups. Conclusion: The experimental HDDMA/TEGDMA-based FRCs might be potential alternatives for bis-GMA-based FRCs.